Madrasah Principal's Strategy in Optimizing Public Relations as a Promotion and Collaboration Tool: A Case Study at the State Islamic Junior High School - Eci Sriwahyuni; Dody Putra; Ona Yulita; Khairul Anwar; Raveenthiran Vivekanantharasa (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Madrasah Principal's Strategy in Optimizing Public Relations as a Promotion and Collaboration Tool: A Case Study at the State Islamic Junior High SchoolObjective: This study aims to determine the madrasah principal's strategy in optimizing public relations as a promotional and collaborative tool at MTsN Padang Panjang. Method: This research uses a case study method. Data were collected through observation and interviews. Data analysis followed the Miles and Huberman model. Results: The strategies applied by the madrasah principal in optimizing public relations include using social media for publications, open communication via WhatsApp, collaboration with external parties, and social activities with the community. Conclusion: The active role of public relations in communication and collaboration is key to building and maintaining the school's image as an educational institution. Contribution: This research contributes as a model of public relations strategy that integrates digital technology in promotion and collaboration in madrasah, as well as a reference for other schools.INDONESIAN: Strategi Kepala Madrasah dalam Mengoptimalkan Humas sebagai Alat Promosi dan Kolaborasi: Studi Kasus di Madrasah Tsanawiyah NegeriTujuan: Penelitian ini bertujuan untuk mengetahui strategi kepala madrasah dalam mengoptimalkan humas sebagai alat promosi dan kolaborasi di MTsN Padang Panjang. Metode: Penelitian ini menggunakan metode studi kasus. Data dikumpulkan melalui observasi, wawancara. Analisis data mengikuti model Miles dan Huberman. Hasil: Strategi yang diterapkan kepala madrasah dalam mengoptimalkan Humas meliputi penggunaan media sosial untuk publikasi, komunikasi terbuka via WhatsApp, kolaborasi dengan pihak eksternal, dan kegiatan sosial dengan masyarakat. Kesimpulan: Peran aktif humas dalam komunikasi dan kolaborasi menjadi kunci dalam membangun dan mempertahankan citra sekolah sebagai lembaga pendidikan. Kontribusi: penelitian ini berkontribusi sebagai model strategi humas yang mengintegrasikan teknologi digital dalam promosi dan kolaborasi di madrasah, serta sebagai acuan bagi sekolah lain.